2011
DOI: 10.1266/ggs.86.27
|View full text |Cite
|
Sign up to set email alerts
|

Variability of sexual organ possession rates and phylogenetic analyses of a parthenogenetic Japanese earthworm, Amynthas vittatus (Oligochaeta: Megascolecidae)

Abstract: Although earthworms are hermaphroditic animals with biparental sexual reproduction, some parthenogenetic species have been found. Evolutionary trends in parthenogenetic earthworms revealed a reduction in the reproductive organs. To clarify the phylogenetic relationships of parthenogenetic earthworms with different degree of degraded reproductive organs, we conducted a morphological analysis of the reproductive organs and molecular phylogenetic analyses of Amynthas vittatus which usually degraded a part of repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…In the present study, lineage A was at the terminal node too. Additionally, the time of divergence for lineage A (0.48 Ma; 95%: 0.22-0.53 Ma) was later than for lineage B (0.72 Ma; 95%: 0.29-1.47 Ma), indicating that these unisexual forms did indeed arise from sexual congeners, which was in accordance with previous findings [28,53,77].…”
Section: Parthenogenesis and The Demographic And Dispersal Of A Triasupporting
confidence: 91%
“…In the present study, lineage A was at the terminal node too. Additionally, the time of divergence for lineage A (0.48 Ma; 95%: 0.22-0.53 Ma) was later than for lineage B (0.72 Ma; 95%: 0.29-1.47 Ma), indicating that these unisexual forms did indeed arise from sexual congeners, which was in accordance with previous findings [28,53,77].…”
Section: Parthenogenesis and The Demographic And Dispersal Of A Triasupporting
confidence: 91%
“…22) Therefore, we used an internationally recognized method to analyze the COI region. [22][23][24] Phylogenetic analysis showed that all three strains differed to one another (Fig. 1).…”
Section: Characterization Of Earthworms By Morphological and Phylogenmentioning
confidence: 99%
“…Two major explanations suggested for the low level of polymorphism in A. icterica were the occurrence of recent population bottlenecks and/or recurrent inbreeding due to reproduction between relatives. In addition, parthenogenesis could be possibly another cause, as there are some parthenogenetic species reported in the Megascolecidae (Díaz Cosín et al, 2011, Minamiya et al, 2011, the family to which Pontodrilus belongs. In contrast, a low genetic distance has also been reported in Thai terrestrial earthworms, where Prasankok et al (2013) reported that Metaphire peguana had a high degree of gene flow (allozyme and mtCOI) between populations across the different geographic regions.…”
Section: Discussionmentioning
confidence: 99%